Association of Acinetobacter Baumannii with invasive procedures in hospitalized patients in Jakarta - Lucky H Moehario; Tasia Esterita; Valencia Shirleen; Thomas Robertus; Yohanna Angelina (Journal of Infection in Developing Countries)
Introduction: Acinetobacter baumannii, a multidrug-resistant Gram-negative opportunist has been known among the cause of nosocomial infection. Risk factors of infection related to A. baumannii have been reported elsewhere. This study aimed to find the association of A. baumannii positive culture and invasive procedures in patients hospitalized in the Intensive Care Unit and Hospital ward in Jakarta.